The ecology of natural capital accounting. (7th January 2019) - Mace, Georgina M
Abstract: Natural capital is increasingly widely discussed and included in corporate and governmental accounts, using a variety of different approaches and metrics. Here I argue that natural capital is fundamentally an emergent feature of structures and functions of the natural environment. Therefore its valuation and metrics for reporting on its condition and the way that it is represented in accounts need to reflect these defining features and not rest solely on measurable flows of goods and services. Natural capital is an asset, and its many contributions to the economy and society, often called ecosystem services, are both malleable and adaptable. Their value changes with time and context as they become more or less important and relevant for particular purposes. Unlike most produced assets, natural assets are multifunctional, adaptable, and resilient, and within limits they have the capacity to regrow or reorganize themselves. Maintaining this capacity is therefore the key priority for a responsible owner or manager of natural assets. Currently most metrics for natural capital are based on the quality or quantity of flows of goods and services, on the geographical distribution of particular ecosystems or land/sea uses, and by reference to ecosystem services delivered by particular ecosystems. The advantages and disadvantages of these different approaches are discussed, but I propose instead using the quality of fundamental ecological processes and functions which properly represent the functioning and capabilities of the natural capital system upon which society and the economy depend.